ANALISIS STRATEGI PENERAPAN GREEN COMPUTING DI POLITEKNIK NEGERI SUBANG - Nunu Nugraha Purnawan; Rian Piarna; Rita Purwasih (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
State Polytechnic of Subang (POLSUB) with the core business in education has the main activity in the form of academic management. The main activities and supporters are inseparable from the use of Information and Communication Technology (ICT) equipment, that can help and facilitate work. Current use of ICT, according to Greenpeace, also plays a role in environmental damage. POLSUB as a new state university, wisely applying ICTs requires an IT strategic plan. Strengths-Weakness-Opportunities-Threats (SWOT) and IT-Balance Scorecard (IT-BSC) methods are used to get a strategic plan for the creation of Green Computing in the daily activities of the campus environment. The results of the SWOT analysis obtained a total weight score of Internal Factor Evaluation (IFE) 2.72 representing average internal position and a total score of weight 2.68 External Factor Evaluation (EFE) representing a medium external position. Based on the results of the Threats-Opportunities-Weakness-Strengths (TOWS) matrix analysis obtained ten strategic proposals, which were then grouped into four IT-BSC perspectives. Keywords: Green Computing, Information and Communication Technology, IT-Balanced Scorecard, SWOT.